Youth and age in the medieval north - Lewis-Simpson, Shannon (Northern world, 2008)
Following from themes explored during the 2005 International Medieval Congress on 'Youth and Age', this volume focuses upon social, cultural and biological aspects of being young and old in the medieval north. It showcases the diverse issues that surround interdisciplinary studies of youth and age.